New Aspects Concerning the Ampicillin Photodegradation - Radu Cercel; Mirela Paraschiv; Cristina Stefania Florica; Monica Daescu; Adelina Udrescu; Romeo C. Ciobanu; Cristina Schreiner; Mihaela Baibarac (MDPI AG, 2022)
New aspects concerning the photodegradation (PD) of ampicillin are reported by photoluminescence (PL), Raman scattering and FTIR spectroscopy. The exposure of ampicillin in the absence (AM) and in the presence of the excipient (AMP) to UV light leads to an intensity diminution of the photoluminescence excitation (PLE) and photoluminescence (PL) spectra and the emergence of a new IR band at 3450 cm−1. The photoluminescence studies demonstrate that the AM PD is amplified in the presence of excipients and an alkaline medium. In this last case, the PD process of AM involves the emergence of new compounds, whose presence is highlighted by: (i) the emergence of the isosbestic point at 300 nm in the UV-VIS spectra; (ii) a change in the ratio between the absorbance of IR bands situated in the spectral ranges 1200-1660 and 3250-3450 cm−1; and (iii) a change in the ratio between the intensities of the Raman lines localized in the spectral ranges 1050-1800 and 2750-3100 cm−1. A chemical mechanism of the PD processes of AM in an alkaline medium is proposed.